BIOM-49. A PILOT STUDY OF CEREBROSPINAL FLUID EXOSOMAL SMALL RNA-SEQUENCING IN PEDIATRIC MEDULLOBLASTOMA PATIENTS ON THE NEXT CONSORTIUM "HEAD START" 4 PROTOCOL. (14th November 2022) - Bell, Erica; Webb, Amy; Stanek, Joseph; Blue, Megan; Patel, Parth; Thomas, Diana; Pierson, Christopher; Mladkova, Nikol; Fleming, Jessica; Miller, Katherine; Grischow, Olivia; Liszkay, Thomas; et al.
Abstract: BACKGROUND: Head Start 4 is a randomized clinical trial to determine whether dose-intensive tandem consolidation, compared with a single cycle, with autologous hematopoietic progenitor cell rescue provides a survival benefit in pediatric patients with medulloblastoma or other embryonal tumors. The trial incorporates upfront molecular subgrouping and non-mandatory, prospective blood and cerebrospinal fluid (CSF) collection. This pilot study aimed to identify exosomal non-coding RNAs (exo-ncRNAs) that might serve as novel diagnostic and/or treatment response biomarkers. METHODS: CSF(1-2mLs) from 11 controls (non-tumor) and 27 medulloblastoma participants including 23 obtained at baseline, 22 at the end of induction, 3 post-consolidation, and 4 relapse time points, were profiled. Exosome isolation and small RNA-sequencing were performed by System Biosciences. Differential gene expression (DGE) was performed in R (DESeq2). Variations in gene expression profiles between samples were visualized using principal component analysis. RESULTS: After limiting to ncRNAs with expression of 2 counts per million in 50% or more of the samples in each comparison, ~9, 500 ncRNAs were detected. DGE analyses revealed 118 ncRNAs with log2 fold change(FC) >2 and 1 ncRNA with log2FC< -2 in baseline CSF samples compared to controls. In contrast, 11 ncRNAs(log2FC >2) and 1 ncRNA(log2FC< -2) were detected in end of induction CSF samples compared to controls. Comparing end of induction to baseline CSF samples accounting for paired samples, 0 ncRNAs(log2FC >2) and 52 ncRNAs(log2FC< -2) were detected. CONCLUSIONS: Overall, our data indicate that exosomal small RNA-sequencing of limited CSF volumes is feasible. Differential expression and distinct clustering between tumor baseline samples compared to non-tumor controls was observed. CSF-derived exo-ncRNAs at end of induction also demonstrated "normalization" of ncRNA profiles, signifying CSF biomarkers may serve a role in diagnosis and molecular response assessment. A comprehensive analysis including multi-marker predictive model development and molecular subgrouping will be undertaken at completion of study enrollment.